EMPLOYEE MOTIVATION IN THE VUCA ERA (VOLATILITY, UNCERTAINTY, COMPLEXITY, AMBIGUITY): A SYSTEMATIC REVIEW OF DETERMINING FACTORS AND ORGANIZATIONAL STRATEGIES - Ranny Fitria Puspitasari; Aulia Ramadhani; Sopiah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era has fundamentally reshaped the organizational landscape, necessitating adaptive and responsive employee motivation strategies. This study aims to identify and analyze the key determinants of employee motivation and effective organizational strategies in navigating the dynamics of the VUCA environment. Employing a Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol, 25 peer-reviewed articles indexed in Scopus (2019–2024) were analyzed thematically and narratively. The findings indicate that employee motivation is shaped by five core dimensions: psychological conditions and job expectations, agile leadership, adaptive organizational culture, continuous learning, and coaching. Effective organizational strategies include empowerment, value-based incentives, a collaborative culture, and the integration of motivation theories into human resource policies. This study extends the applicability of classical motivation theories within contemporary organizational contexts and offers practical guidance for designing work systems that are human-centric, flexible, and sustainable. The findings emphasize the importance of integrated and contextually grounded motivation strategies in reinforcing organizational resilience amid global uncertainty.